Glyphosate: Human Exposure and Health Impacts — A Literature Review - Aleksandra Słojewska; Mikołaj Łabuda; Klaudia Królikowska; Adrianna Bogucka; Teresa Sowińska; Oliwia Mentel; Jakub Sikora; Karolina Knychalska; Agata Kotkowiak; Agnieszka Szema (Journal of Education, Health and Sport)
Introduction and Purpose: Glyphosate is the most widely used herbicide globally, primarily due to its effectiveness and compatibility with genetically modified (GM) crops. Its non-selective action on the shikimate pathway makes it suitable for widespread use in agriculture, urban areas, and water management. However, growing concerns have emerged over its potential health effects, particularly following its classification by IARC in 2015 as "probably carcinogenic to humans." This review aims to examine current knowledge on glyphosate exposure, its environmental prevalence, human biomonitoring data, and associated health risks.